Tissue-specific distribution of organotin and booster biocides in marine organisms from seagrass area of Pulai River Estuary, Malaysia - Mukhtar, Aqilah; Zulkifli, Syaizwan Zahmir; Harino, Hiroya; Ismail, Ahmad (Springer Science and Business Media LLC, 2026)
Organotin (OT) compounds, historically dominant in antifouling paints, are persistent organic pollutants known for their severe endocrine-disrupting toxicity. While the global ban on OT shifted to the usage of alternative booster biocides, the environmental behavior, tissue-specific partitioning, and persistence of the replacement compounds remain understudied, particularly in tropical estuarine ecosystems. This study investigates the concentrations and accumulation patterns of OT species of butyltin, known as monobutyltin (MBT), dibutyltin (DBT), tributyltin (TBT), phenyltins of monophenyltin (MPT), diphenyltin (DPT), triphenyltin (TPT), and alternative booster biocides of diuron, dichlofluanid, chlorothalonil, Irgarol 1051, M1, and Sea-Nine 211 across a multitrophic system including seagrass (Enhalus acoroides), bivalves (Pinna bicolor), and two fish species (Thryssa dussumieri and Otolithus ruber) in Pulai River Estuary, Malaysia. Results indicated a shift in pollutant dominance, in which TPT showed higher accumulation between 18.62 and 652.48 µg/kg compared to TBT, with values from 4.05 to 403.47 µg/kg. This suggests that phenyltins currently exhibit higher bioaccumulation potential or persistence in local biota compared to butyltins. Degradation products were also ubiquitously detected, with MBT and DBT ranging from 1.12 to 290.22 µg/kg, and MPT and DPT ranging from 5.13 to 7494.74 µg/kg. Among alternative booster biocides, high concentrations of dichlofluanid, M1, and Sea-Nine 211 were detected in fish cardiac tissues with respective values of 6422.01 µg/kg, 3970.97 µg/kg, and 1495.82 µg/kg. Tissue analysis revealed that Irgarol 1051 and its degradation product M1 were enriched in fish intestines, implicating the ingestion and intestinal absorption of contaminated prey or sediment particles as the primary pathway rather than gill respiration, while detection in seagrass roots indicated sediment-associated exposure. Phenyltins were the dominant OTs, with concentrations exceeding ecological and human health guideline values based on the Oslo and Paris Commission (OSPAR) framework, highlighting trophic transfer and potential consumer risks. A comprehensive monitoring of OTs and booster biocides is strongly recommended to mitigate ecological and human health risks.